“Hidroponik”: Penanaman Life Skill Berwirausaha Sejak Dini - Purwani, Dwi (CV. Supernova Office Stationary and Printing, 2023)
Edurepreneurship is very important to be taught at all levels of education. Everyone has the right to be an entrepreneur, including in Early Childhood Education (PAUD). In the era of globalization, creativity and strong character are needed to face the demands of the times. Character development and creativity need to start from an early age, entrepreneurship is a character that must be encouraged from an early age. The purpose of entrepreneurship education is not only to train prospective entrepreneurs or children to earn money from an early age, but to foster and develop the character that already exists in children. The values that must be implemented through these characters are the values of creativity, innovation, courage, independence and responsibility. TABITA Ujungwatu Kindergarten instills entrepreneurship in children by learning to grow vegetables using hydroponics. Hydroponics is a cultivation technique that does not use soil, but uses water and a nutrient solution that plants need as a growing medium. In hydroponics, apart from water and nutrient solutions, other growing media are also used, such as rock wool, coal, zeolite and many others which are light and sterile.